Optimal Cropping Pattern for Adoption of Micro-Irrigation Methods in Canal Command Area - A Case Study - Gadge, S B; Gorantiwar, S D; Kumar, Virendra; Kothari, Mahesh (Journal of Agricultural Engineering, 2011)
Currently the micro irrigation methods are mainly adopted on farms with irrigation from tube wells or dug wells.However, in view of increasing scarcity of water for irrigation and need to increase food production, it is important to adopt these methods in canal command area. A linear programming model was formulated to suggest the optimal cropping pattern under micro irrigation method in canal command areas. The objective was to achieve the maximum such as net returns. The objective function of the model was subjected to the constraints such as total available water and land during different irrigation periods, crop area restrictions, and system reutilization constraints. The system reutilization constraint facilitated utilization of micro irrigation system among the different short duration seasonal crops having similar system geometry requirement. The model was applied to command area of direct minor no. 3 of the Mula Irrigation Project, Ahmednagar, Maharashtra. The model gave optimal cropping pattern for 431.7 ha of command area having water availability of 171280 mÂ³ during the â€œONâ€ period (7 days) of canal rotation. The net returns from the optimal cropping plan were Rs. 186 million. The optimal cropping pattern allocated 43.17 ha area for papaya, 43.17 ha for sugarcane, 86.35 ha for Kharif brinjal, 259.04 ha for cabbage, 85.35 ha for summer onion and 259.04 ha for summer brinjal. It was found that 6% increase in net benefit could be achieved through reutilization of the micro irrigation systems among the seasonal crops having similar system requirements.